Concentrations of Serum Cyclophilin A in Patients With Bell Palsy - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Background: Cyclophilin A (CyPA) is the responder protein to stimuli that cause inflammation. To date, no association among CyPA and Bell palsy has been reported. Methods: The concentrations of Serum CyPA were measured in 90 healthy participants and 92 patients with Bell palsy. Serum samples of patients and the control group were compared on the basis of CyPA levels. Facial latency and amplitude values on electromyography were evaluated and compared with serum CyPA concentrations. Results: A total of 28, 37, 19, and 8 patients had grade 3, 4, 5, and 6 facial palsy cases, respectively. Comparing the control group and the patient group showed significant differences in CyPA values (P < 0.001). Cyclophilin A value can be evaluated as a marker with high disease discrimination capability. The results also showed that at low CyPA, the average recovery time was shorter than that of high CyPA (41.6 +/- 5.7 days vs 62.8 +/- 10.2 days,P = 0.036). We found no statistically significant relationship between electromyography parameters and CyPA level. (Facial latency:r: -0.014,P: 0.948; facial amplituder: -0.081,P: 0.713). Conclusion: Serum CyPA concentrations increased in response to inflammation in Bell palsy patients. However, CyPA could not be used as an early prognostic marker in Bell palsy, low CyPA indicates the shorter average recovery time than that of high CyPA.
Keywords: Bell palsy; biomarker; cyclophilin A; prognosis; HERPES-SIMPLEX-VIRUS; NUCLEAR TRANSLOCATION; ARTERY-DISEASE; ROCHESTER; PROGNOSIS